Protein-Engineered Large Area Adipose-derived Stem Cell Sheets for Wound Healing. Issue 1 (December 2018) - Na, Jongbeom; Song, Seung; Kim, Jae; Han, Minsu; Heo, June; Yang, Chae; Kim, Hyun; Lew, Dae; Kim, Eunkyoung
Abstract Human adipose-derived stem cells (hADSCs) formed robust cell sheets by engineering the cells with soluble cell adhesive molecules (CAMs), which enabled unique approaches to harvest large area hADSC sheets. As a soluble CAM, fibronectin (FN) (100 pg/ml) enhanced the cell proliferation rate and control both cell-to-cell and cell-to-substrate interactions. Through this engineering of FN, a transferrable hADSC sheet was obtained as a free-stranding sheet (122.6 mm2 ) by a photothermal method. During the harvesting of hADSC sheets by the photothermal method, a collagen layer in-between cells and conductive polymer film (CP) was dissociated, to protect cells from direct exposure to a near infrared (NIR) source. The hADSC sheets were applied to chronic wound of genetically diabeticdb /db micein vivo, to accelerate 30% faster wound closure with a high closure effect (εwc ) than that of control groups. These results indicated that the engineering of CAM and collagens allow hADSC sheet harvesting, which could be extended to engineer various stem cell sheets for efficient therapies.